Laser-Modified Ti Surface Improves Paracrine Osteogenesis by Modulating the Expression of DKK1 in Osteoblasts - Teixeira, Jorge Felipe Lima [UNESP] (2023)
Titanium surface modifications are widely used to modulate cellular behavior by recognition of topographical cues. However, how those modifications affect the expression of mediators that will influence neighboring cells is still elusive. This study aimed to evaluate the effects of conditioned media from osteoblasts cultured on laser-modified titanium surfaces on the differentiation of bone marrow cells in a paracrine manner and to analyze the expression of Wnt pathway inhibitors. Mice calvarial osteoblasts were seeded on polished (P) and Yb:YAG laser-irradiated (L) Ti surfaces. Osteoblast culture media were collected and filtered on alternate days to stimulate mice BMCs. Resazurin assay was performed every other day for 20 days to check BMC viability and proliferation. After 7 and 14 days of BMCs maintained with osteoblasts P and L-conditioned media, alkaline phosphatase activity, Alizarin Red staining, and RT-qPCR were performed. ELISA of conditioned media was conducted to investigate the expression of Wnt inhibitors Dickkopf-1 (DKK1) and Sclerostin (SOST). BMCs showed increased mineralized nodule formation and alkaline phosphatase activity. The L-conditioned media enhanced the BMC mRNA expression of bone-related markers Bglap, Alpl, and Sp7. L-conditioned media decreased the expression of DKK1 compared with P-conditioned media. The contact of osteoblasts with Yb:YAG laser-modified Ti surfaces induces the regulation of the expression of mediators that affect the osteoblastic differentiation of neighboring cells. DKK1 is among these regulated mediators.